PENETAPAN KEBIJAKAN PERIKLANAN ATAS DASAR PERILAKU KONSUMEN (Studi Kasus : Produk Shampoo) - Ismulyana Djan (Jurnal Ilmiah Binaniaga, 2005)
There are three things that should be into consideration in advertising certain product, ic,; the extent of similar products advertised at the same target market and media, cost of advertising, and difficulty in measuring advertising effectiveness. These three factors force management people to launch a market research concerning consumer behavior.Research carried out on 110 respondent asking them to mention: the brand of shampoo they used from ten different alternatives, seven usefulness of that product, and the kind of advertising media that is most often seen, heard, or read, shows that advertising shampoo product should pay attention to the: characteristic of the shampoo user, objective of advertising, target market to be achieved, advertising theme, press media used, and coordination with other marketing factors.That conclusion become the basic formulation on considering advertising policy of shampoo product that pay attention to consumer behavior.